Design, analysis and fabrication of microfluidic devices - Md. Anisur Rahman. (2008)
The main focuses of this research work were to design novel microfluidic devices, to analyze them by developing simulation tools and to fabricate their prototypes. Three novel microfluidic devices, namely a microinjector, a bubble micropump and a diffuser-nozzle micropump have been presented in this thesis. As the performance of the microfluidic devices depend on the method of actuation, several actuation methods have been reviewed. These include piezoelectric, electrostatic, electrohydrodynamic, and thermally bubble driven actuation method. Among these actuation methods, the thermally bubble driven method has been chosen for the microfluidic devices. Both the microinjector and micropumps have been designed with the thermally bubble driven actuation method. The unique characteristics of the proposed microfluidic devices are (i) no moving parts, (ii) high actuation of stroke, (iii) low power consumption, (iv) use of standard IC fabrication techniques, and (v) free from electromagnetic field induced.